IMPLEMENTASI STRATEGI PEMBELAJARAN TUTOR SEBAYA PADA ANAK BERKESULITAN BELAJAR KHUSUS DI SD TAMAN MUDA IBU PAWIYATAN TAMANSISWA - Lena Wati; Siti Anafiah (Universitas Sarjanawiyata Tamansiswa, 2018)
the purpose of this research is to description the implementation of peer tutors learning strategies in learning disabilities at elementary school Taman Muda Ibu Pawiyatan Tamansiswa Yogyakarta. Type of this research is a descriptive qualitative study using instruments of observation, interview and documentation. Data analysis techniques using model Milles and Huberman, namely by means of data collection, data reduction, data display, and conclusion drawing/verification. The results showed that condotioning is done by way of providing clarification of classical learning material, repetition, approach, group, as well as doing the game. Academic development is a further development and understanding. Supporting factors is to help teachers in teh learning process, interaction relationships become better, between teacher and students, ora students with students, students in following the spirit of learning more, dare ask until the creation of a conducive learning atmosphere. Inhibiting factor were the difficulty of determining the tutor, tutor’s lack of preparation, inadequate facilities and infrastructure, as well as seriousness in studying less.